An Acidity‐Unlocked Magnetic Nanoplatform Enables Self‐Boosting ROS Generation through Upregulation of Lactate for Imaging‐Guided Highly Specific Chemodynamic Therapy. (17th March 2021) - Shi, Linan; Wang, Youjuan; Zhang, Cheng; Zhao, Yan; Lu, Chang; Yin, Baoli; Yang, Yue; Gong, Xiangyang; Teng, Lili; Liu, Yanlan; Zhang, Xiaobing; Song, Guosheng
Abstract: Chemodynamic therapy is an emerging tumor therapeutic strategy. However, the anticancer effects are greatly limited by the strong acidity requirements for effective Fenton‐like reaction, and the inevitably "off‐target" toxicity. Herein, we develop an acidity‐unlocked nanoplatform (FePt@FeO x @TAM‐PEG) that can accurately perform the high‐efficient and tumor‐specific catalysis for anticancer treatment, through dual pathway of cyclic amplification strategy. Notably, the pH‐responsive peculiarity of tamoxifen (TAM) drug allows for the catalytic activity of FePt@FeO x to be "turn‐on" in acidic tumor microenvironments, while keeping silence in neutral condition. Importantly, the released TAM within cancer cells is able to inhibit mitochondrial complex I, leading to the upregulated lactate content and thereby the accumulated intracellular H +, which can overcome the intrinsically insufficient acidity of tumor. Through the positive feedback loop, large amount of active FePt@FeO x nanocatalyzers are released and able to access to the endogenous H2 O2, exerting the improved Fenton‐like reaction within the more acidic condition. Finally, such smart nanoplatform enables self‐boosting generation of reactive oxygen species (ROS) and induces strong intracellular oxidative stress, leading to the substantial anticancer outcomes in vivo, which may provide a new insight for tumor‐specific cascade catalytic therapy and reducing the "off‐target" toxicity to surrounding normal tissues. Abstract : A novel acidity‐unlocked and self‐boosting ROS‐generating nanoplatform is facilely developed via assembling FePt@FeO x and tamoxifen. Such smart nanoplatform can provide new insights for enhanced tumor‐specific catalytic therapy with minimal side effects and exert the contrast ability of magnetic resonance and photoacoustic imaging.